(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
A company can put financial information toward the internet to reach a broader audience worldwide, faster and cheaper. This research aims to analyze the practicality of internet financial reporting and its factors. The samples are forty-five companies that entered into the calculation of LQ45 shares on the Indonesia Stock Exchange during the 2018 year. After passing of purposive sampling, validity samples are thirty-nine firms. Data were collected by documents and literature of the company, especially the focus on Indonesian stock exchange, and were analysed by the multiple linear regression technique. Research findings show that some variables, such as public ownership and group industry, aren’t significantly influenced by applied internet financial reporting.